АНАЛІТИЧНИЙ МЕТОД ФОРМУВАННЯ ІНТЕГРОВАНИХ ДИНАМІЧНИХ МОДЕЛЕЙ ТА ЇХ ПРОГРАМНА РЕАЛІЗАЦІЯ - Sytnik, Aleksandr Alekseevich (Kamianets-Podilskyi National Ivan Ohiienko University, 2012)
In represented work the integral method of dynamic objects simulation is considered. It is shown, that the offered method has a large generality and allows to decide on wide scientific fields of problems of mathematical simulation, which can be described with the integral equations. It is marked, that the offered approach allows to use new numerical algorithms, the number of traditional problems solving by means of computer aided simulation. The universal software for the solution of integral equations in MATLAB is developed.